2021
DOI: 10.1136/bmjgh-2021-005578
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood development and parental training interventions in rural China: a systematic review and meta-analysis

Abstract: IntroductionInadequate care during early childhood can lead to long-term deficits in skills. Parenting programmes that encourage investment in young children are a promising tool for improving early development outcomes and long-term opportunities in low-income and middle-income regions, such as rural China.MethodsWe conducted a systematic review and a meta-analysis to investigate the prevalence of early developmental delays and stimulating parenting practices as well as the effect of parental training program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
53
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 63 publications
3
53
0
3
Order By: Relevance
“…Research has shown that there are high rates of cognitive and non-cognitive developmental delays in children under the age 5 in rural China [ 1 , 2 , 3 , 4 ]. According to a systematic review by Emmers et al (2021), nearly 45% and 36% children under age 5 have delays in cognitive and social–emotional skills, respectively [ 5 ]. Due to high brain plasticity in the first years of life, the developmental outcomes at this age are critical to the development of more complex cognitive and social–emotional skills in later childhood and even to the levels of educational attainment and employment in adulthood [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has shown that there are high rates of cognitive and non-cognitive developmental delays in children under the age 5 in rural China [ 1 , 2 , 3 , 4 ]. According to a systematic review by Emmers et al (2021), nearly 45% and 36% children under age 5 have delays in cognitive and social–emotional skills, respectively [ 5 ]. Due to high brain plasticity in the first years of life, the developmental outcomes at this age are critical to the development of more complex cognitive and social–emotional skills in later childhood and even to the levels of educational attainment and employment in adulthood [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, studies have shown that parenting practices are poor in rural China when children are under the age of 5 [ 1 , 4 , 5 , 21 , 22 ]. According to the research, only 23% of caregivers read books to their children, and only 25% of caregivers tell stories to their children [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children in rural areas of China aged 0–3 years are seriously lagging in their development [ 7 , 8 , 9 , 10 ]. The percentage of children with at least one lag in their development of cognitive, language, motor, and social-emotional skills is 86% [ 11 ], and the risk of cognitive, language, motor, and social-emotional delays in children is 53%, 60%, 36%, and 40%, respectively [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, caregivers with poor mental health also have negative impacts on their children in terms of cognitive development, language development, social emotions, adaptability, and behavior [ 19 , 24 , 29 , 30 , 31 , 32 , 33 ]. Some 36–46% of children under the age of five are stunted and have slower early cognitive, language, and social-emotional development in low- and middle-income rural areas of West-central China [ 7 ]. These delays are positively correlated with negative parenting behavior [ 16 , 34 ].…”
Section: Introductionmentioning
confidence: 99%